A rapid national survey of terrestrial and semi-aquatic mammals using environmental DNA metabarcoding - Holly A. Broadhurst; Elin E. Smith; Jake M. Jackman; Robert Raynor; Claire Howe; Naiara Guimarães Sales; Allan D. McDevitt (Mammalian Biology, 2026)
Assessing the distribution and diversity of terrestrial and semi-aquatic mammals is fundamental for effective conservation efforts. Environmental DNA (eDNA) metabarcoding has emerged as a rapid and cost-effective method for surveying mammals. It has promising avenues for conducting national surveys and enabling comprehensive assessments of mammalian populations across diverse habitats. We collected eDNA samples from 60 water systems across six regions in England (from north to south), United Kingdom, over a period of up to four days in each region. We detected 26 mammals from five taxonomic orders across all sampling locations, recovering 53–89% of the known mammal community in each region. Our findings underscore the feasibility of utilising eDNA metabarcoding for rapidly surveying mammal populations on a national scale, potentially complementing data from existing surveys/records or implementing in data deficient regions. However, challenges remain for surveying certain species using this method, with varying levels of detectability of key species (e.g. otters) across regions.

Extracellular electron transfer by the cultured coral photosymbiont Symbiodinium microadriaticum - Loris Marcel; James T. Simon; Joshua M. Lawrence; Svetlana Menkin; Adrian C. Barbrook; R. Ellen R. Nisbet; Christopher J. Howe; Jenny Z. Zhang (Photosynthesis Research, 2026)
Photosynthetic microorganisms may show extracellular electron transfer (EET), in which some of the electrons generated by photosynthesis or respiration are lost from the cell. Most studies have focussed on cyanobacteria, with very few on eukaryotic algae. Here we demonstrate EET from the eukaryotic dinoflagellate alga Symbiodinium microadriaticum , a species that can form symbiosis with corals and other Cnidaria. We show that the EET involves diffusible electroactive species, which may represent a previously unsuspected route for communication between symbionts and hosts. We show that EET can be used to study photosynthetic and respiratory functions in the dinoflagellate. We also show that it can provide information on the effects of environmental stresses including changes in temperature (linked to coral bleaching), pH and light intensity. The electrochemical platform outlined in this study offers a novel tool for studying dinoflagellate physiology, the coral-dinoflagellate symbiosis, and the molecular mechanisms of bleaching.

Candidozyma auris Reported in Scotland: a Call for Vigilance Amid Global Rise - M. H. Howe; K. L. Bartie; W. G. Mackay; T. Inkster; S. Cairns; R. Kean; A. M. Bal; G. Ramage (Mycopathologia, 2026)
Candidozyma auris (formerly Candida auris ) is an emerging pathogenic yeast associated with healthcare outbreaks worldwide. Despite increasing reports across Europe, no published data have previously described cases in Scotland. Here, we report the first detections of C. auris in Scotland, as submitted to ARHAI Scotland. Eight cases (seven colonisations, one infection) were identified to date across four NHS Scotland boards, all linked to repatriation or recent hospitalisation abroad. To contextualise these findings, we reviewed publicly available literature and surveillance data for Western and Northern Europe, identifying considerable variation in case numbers and highlighting Scotland’s position among countries with the lowest reported cases. All Scottish cases were imported, underscoring the importance of targeted screening of patients with international healthcare exposure. These findings inform preparedness planning and support recommendations for strengthened surveillance to prevent onward transmission.

Habitat structure and landscape context influence vocalising vertebrates in oil palm plantations - Erin K. Wills; Caitlin S. Willis; Reza Azmi; Dominique A. Potvin; Baizul Hafsyam Badli-Sham; John Howes; Catherine M. Yule; Ben L. Gilby (Biodiversity and Conservation, 2026)
As global food demand rises with population growth, much of the expected land conversion to agriculture is projected to occur in tropical biodiversity hotspots. Balancing food production and biodiversity conservation requires managing agricultural landscapes to serve both goals. To support this, we examined how animal distribution in an oil palm plantation is influenced by landscape context and habitat structure. The study was conducted in Johor, Malaysia, a region dominated by oil palm agriculture. Passive acoustic recorders were deployed across 35 sites within a 1160-hectare oil palm plantation, encompassing a range of yield levels, and distances to natural features. Recordings were collected periodically during the inter-monsoonal period, April-May 2025, targeting peak seasonal and circadian vocal activity of birds and anurans, and analysed using BirdNET and manual spectrogram inspection to identify birds, anurans, and mammals. A total of 89 vertebrate species (75 birds, 12 anurans, 2 mammals) were detected, including several threatened species. Species richness was greatest at sites with taller canopies, lower frond cover, and closer proximity to water and forests, highlighting the importance of maintaining structural complexity and connectivity to maximise biodiversity within plantations. Exploratory analysis found no significant relationship between bird richness, including frugivores, and palm oil yield, thereby suggesting limited short-term effects, though extended studies are required to evaluate longer-term biodiversity influences on production. To enhance biodiversity, we recommend replanting native trees on low-yield blocks, enhancing vertical structure with tree islands, and maintaining clean waterways, while keeping frond stacking to

Analysis of IgG responses to Sarcocystis neurona in horses with equine protozoal myeloencephalitis (EPM) suggests a Th1-biased immune response - Catherine J. Angwin; Izabela de Assis Rocha; Stephen M. Reed; Jennifer K. Morrow; Amy Graves; Daniel K. Howe (Veterinary Immunology and Immunopathology, 2025)

Soft Range Limits Shape Sensitivity to Forest Cover More Strongly Than Hard Range Limits - Natasha R. Granville; Alex L. Pigot; Benjamin Howes; Luiz dos Anjos; Victor Arroyo‐Rodriguez; Luc Barbaro; Jos Barlow; Matthew G. Betts; Alexis Cerezo; Pedro F. Develey; Jack H. Hatfield; Hervé Jactel; et al. (Global Ecology and Biogeography, 2025)
Aim Land‐use change is a major threat to biodiversity, yet there remains considerable unexplained variation in how it affects different populations of the same species. Here, we examine how sensitivity to forest cover changes depending on proximity to different limits of a species' range. By comparing responses as species approach their coastal (‘hard’) and inland (‘soft’) range limits, we aim to provide insight into the relative influence of mass effects, as compared to abiotic and biotic environmental suitability in shaping population sensitivity. Location Global. Time Period 1996–2019. Major Taxa Studied Birds. Methods We combined data from several large databases to obtain a dataset of 2543 bird species surveyed across 116 studies, spanning six continents. Using expert‐verified range maps, we calculated the position of populations relative to their species' nearest inland (‘soft’) and coastal (‘hard’) range limits and categorised the inland limits as equatorward‐ or poleward‐ facing. We investigated how distance to range limits and forest cover, derived from a 30 m‐resolution global dataset, affect the probability of species' incidence. Results We found that bird populations are more sensitive to forest cover when located closer to their species' inland (‘soft’) range limits, whereas this was not the case at coastal (‘hard’) range limits. The heightened sensitivity to forest cover at soft range limits was similar regardless of whether the range limit faced equatorward or poleward. Main Conclusions These results highlight how populations close to the soft limits of their species' ranges are at higher risk of extirpation resulting from loss of forest cover. This suggests that environmental conditions (e.g., climate), which become more challenging away from the core of the species' range, drive variability in sensitivity to forest cover.

Extreme Heatwave Causes Immediate, Widespread Mortality of Forest Canopy Foliage, Highlighting Modes of Forest Sensitivity to Extreme Heat - Adam Sibley; Christopher Still; Matthew Gregory; Constance Harrington; David Shaw; Nina Ferrari; Alex Dye; Mark Schulze; Glenn Howe; David E. Rupp; Christopher Daly; Daniel DePinte; et al. (Global Change Biology, 2025)
In late June 2021, multiple days of record‐breaking heat caused an unprecedented amount of foliage death in the forests of the Pacific Northwest, USA. Portions of tree canopies with healthy green foliage prior to the heat changed to red or orange shortly after the event. The change in foliage color could be readily seen in satellite imagery and was corroborated as foliar death (heat scorch) by aerial surveys and extensive observations on the ground. To better understand the patterns and processes driving foliar death, we used satellite imagery to identify 293,546 ha of forest, or ~4.7% of forest area, that were damaged in western Oregon and Washington by this extreme heat event. Analysis of underlying drivers of the observed heat damage indicated greater sensitivity was related to abiotic factors such as sun exposure, aspect, and microclimate, as well as biotic factors like tree species and stand age, budburst phenology, and foliar pathogens impacting tree health. Iconic, culturally and economically significant species like western redcedar, western hemlock, and Sitka spruce were disproportionately sensitive to heat damage, including in old‐growth stands where they are canopy dominants. These findings highlight the multifaceted challenges posed to forests by extreme heat waves, and the need to better understand their impact on forest ecosystems in a rapidly warming climate.

Alignment between Duplex Sequencing and transgenic rodent mutation assay data in the assessment of in vivo NDMA-induced mutagenesis - Anne L. Ashford; Daniela Nachmanson; John W. Wills; Jacob E. Higgins; Thomas H. Smith; Kevin C. Vavra; Farah A. Dahalan; Jonathan Howe; Joanne M. Elloway; Jesse J. Salk; Ann Doherty; Anthony M. Lynch (Archives of Toxicology, 2025)

Apicomplexan and non-metazoan microeukaryotes in the thermosensitive reef-building coral Acropora hyacinthus shift in abundance throughout an extreme coral bleaching event - Athena Peterson; Sunni Patton; Emily R. Schmeltzer; Carsten G. B. Grupstra; Lauren I. Howe-Kerr; J. Grace Klinges; Rebecca L. Maher; Adriana Messyasz; Sarah Seabrook; Andrew R. Thurber; Adrienne M. S. Correa; Rebecca L. Vega Thurber (Frontiers in Marine Science, 2025)
Coral reefs play vital roles in global marine systems and are currently facing increased threats of bleaching. Coral bleaching is heavily influenced by the host-associated microeukaryote community – most notably the dinoflagellate family Symbiodiniaceae. The apicomplexan family Corallicolidae, is the second most abundant member of the microeukaryote community, yet their role in coral health is largely unknown. To explore the role that this apicomplexan and the greater non-metazoan microeukaryotic community play in coral health, samples of a thermally sensitive scleractinian coral, Acropora hyacinthus , were collected over the course of a severe coral bleaching event and its aftermath. Through 18S rRNA gene sequencing analysis, we found that taxa within the family Corallicolidae were relatively enriched in corals during, and immediately after, the severe bleaching event as compared to before or one year after. Although utilizing 18S rRNA gene sequencing methods is not the standard for Symbiodiniaceae community profiling, we were able to observe symbiont shuffling among the Symbiodiniaceae communities, as the dominant algal symbiont shifted from the genus Cladocopium to the genus Symbiodinium following the bleaching event. Furthermore, the non-metazoan microeukaryote community displayed a general shift towards a state of dysbiosis; evidenced by substantial changes in both microeukaryote community composition and dispersion. These results offer insight into the dynamics of apicomplexans throughout the course of an increasingly common global coral reef stressor.

Prenatal per- and polyfluoroalkyl substance mixtures and weight for length from birth to 12 months: The New Hampshire Birth Cohort Study - Gyeyoon Yim; Caitlin G. Howe; Lisa G. Gallagher; Diane Gilbert-Diamond; Antonia M. Calafat; Julianne Cook Botelho; Margaret R. Karagas; Megan E. Romano (Science of The Total Environment, 2025)

Working memory processes and the histamine-3 receptor in schizophrenia: a [11C]MK-8278 PET-fMRI study - Atheeshaan Arumuham; Ekaterina Shatalina; Matthew M. Nour; Mattia Veronese; Ellis Chika Onwordi; Stephen J. Kaar; Sameer Jauhar; Eugenii A. Rabiner; Oliver D. Howes (Psychopharmacology, 2025)
Rationale Working memory impairment is a prominent feature of schizophrenia which predicts clinical and functional outcomes. Preclinical data suggest histamine-3 receptor (H3R) expression in cortical pyramidal neurons may have a role in working memory, and post-mortem data has found disruptions of H3R expression in schizophrenia. Objectives We examined the role of H3R in vivo to elucidate its role on working memory impairment in schizophrenia. Methods We used positron emission tomography (PET) with the selective H3R radioligand [ 11 C]MK-8278 to measure H3R availability, and employed a task during functional magnetic resonance imaging (fMRI) to assess working memory-evoked brain activation and cognitive task performance, in patients with schizophrenia ( n = 12) and matched healthy volunteers ( n = 12). We assessed the relationship between H3R availability and both task performance and working memory-evoked brain activation in regions of interest (ROIs), including the anterior cingulate cortex (ACC) and dorsolateral prefrontal cortex (DLPFC). Results Patients with schizophrenia showed a strong positive correlation, after corrections for multiple comparisons, between ACC H3R availability and task performance (rho = 0.73, p = 0.007), which was absent in the control group (rho = 0.03, p = 0.94). Further ROI analysis did not find a significant relationship between H3R availability and working memory-evoked brain activation. Conclusions These results provide support for the role of H3R on working memory processes in patients with schizophrenia.

Prenatal per- and polyfluoroalkyl substances and blood pressure trajectories in the New Hampshire Birth Cohort Study - Yuting Wang; Elizabeth C. Anderson; Caitlin G. Howe; Jiang Gui; Lisa G. Gallagher; Brianna Heggeseth; Julianne Cook Botelho; Antonia M. Calafat; Margaret R. Karagas; Megan E. Romano (International Journal of Hygiene and Environmental Health, 2025)

Brushite: a Reclaimed Phosphorus Fertilizer for Agricultural Nutrient Fertilization - Harrison R. Coker; Rui Yang; Isaiah J. Robertson; Joshua M. Doria; Katie L. Lewis; Julie A. Howe (Journal of Soil Science and Plant Nutrition, 2025)
Phosphorus fertilizers are typically produced from mined and chemically processed rock phosphate, which is a diminishing non-renewable resource. Wastewater-reclaimed phosphorus minerals, such as brushite (CaHPO 4 ·2H 2 O), have the potential to be utilized as agricultural fertilizers. The commercial recovery of brushite from wastewater processing is a recent advancement; however, its efficacy as an agricultural fertilizer has yet to be evaluated. Wastewater-reclaimed brushite was tested in a greenhouse and field setting. In the greenhouse study, two P-limited soils were used to grow corn fertilized using brushite and were compared with struvite (NH 4 MgPO 4 ·6H 2 O), another reclaimed P source, and conventional P fertilizers, triple super phosphate (TSP) and monoammonium phosphate (MAP). In the field, corn, wheat, and cotton were grown in two ecoregions for two sites years to compare brushite and struvite with conventional fertilizers. Plants were evaluated for P uptake and yield, and P availability was determined as extractable P. Results indicate that brushite promoted plant productivity similar to conventional fertilizers in P-limited greenhouse soils. Field studies demonstrated similar uptake and assimilation of brushite-P compared to synthetic fertilizers and struvite. Soil acidification occurred across all fertilization treatments. The use of reclaimed brushite as a P fertilizer appears to be as effective as commercially available synthetic fertilizers.

The role of ocean circulation and regolith removal in triggering the Mid-Pleistocene Transition: Insights from authigenic Nd isotopes - Thomas J. Williams; Alexander M. Piotrowski; Jacob N.W. Howe; Claus-Dieter Hillenbrand; Claire S. Allen; Josephine A. Clegg (Quaternary Science Reviews, 2024)

Organophosphate ester flame retardant chemicals and maternal depression during pregnancy - Ixel Hernandez-Castro; Sandrah P. Eckel; Caitlin G. Howe; Max T. Aung; Kurunthachalam Kannan; Morgan Robinson; Helen B. Foley; Tingyu Yang; Mario J. Vigil; Xinci Chen; Brendan Grubbs; Laila Al-Marayati; et al. (Environmental Research, 2024)

Relative humidity, temperature, and hypertensive disorders of pregnancy: Findings from the Project Viva cohort - Christina M. Howe; Brent A. Coull; Stefania Papatheodorou; Heike Luttmann-Gibson; Sheryl L. Rifas-Shiman; Ander Wilson; Itai Kloog; Qian Di; Antonella Zanobetti; Petros Koutrakis; Joel D. Schwartz; Emily Oken; et al. (Environmental Research, 2024)

High-resolution, precision mapping of seagrass blue carbon habitat using multi-spectral imaging and aerial LiDAR - Anders Ekelund; Andy Waddington; S. David Harris; Wells Howe; Carl Dersell; Erik Josefsson; Julian Olszewski; Torbjörn Tingåker; Eric Yang; Carlos M. Duarte; Austin J. Gallagher (Estuarine, Coastal and Shelf Science, 2024)

Mitigating municipal solid waste fouling in biofuel conversion via screw surface modifications - Xin He; Jens T. Darsell; Jaya Shankar Tumuluru; Wenbo Wang; Harry M. Meyer; James R. Keiser; Aashish Rohatgi; Daniel T. Howe; Jun Qu (Biomass and Bioenergy, 2024)

Association of diet with per- and polyfluoroalkyl substances in plasma and human milk in the New Hampshire Birth Cohort Study - Yuting Wang; Jiang Gui; Caitlin G. Howe; Jennifer A. Emond; Rachel L. Criswell; Lisa G. Gallagher; Carin A. Huset; Lisa A. Peterson; Julianne Cook Botelho; Antonia M. Calafat; Brock Christensen; Margaret R. Karagas; et al. (Science of The Total Environment, 2024)

The test–retest reliability of physiological and perceptual responses during treadmill load carriage - Danielle M. Vickery-Howe; Ben J. Dascombe; Anthea C. Clarke; Jace R. Drain; Minh Huynh; Kane J. Middleton (European Journal of Applied Physiology, 2024)
Purpose Understanding the test–retest reliability of physiological responses to load carriage influences the interpretation of those results. The aim of this study was to determine the test–retest reliability of physiological measures during loaded treadmill walking at 5.5 km h −1 using the MetaMax 3B. Methods Fifteen Australian Army soldiers (9 male, 6 female) repeated two 12-min bouts of treadmill walking at 5.5 km h −1 in both a 7.2 kg Control condition (MetaMax 3B, replica rifle) and a 23.2 kg Patrol condition (Control condition plus vest) across three sessions, separated by one week. Expired respiratory gases and heart rate were continuously collected, with the final 3 min of data analysed. Ratings of Perceived Exertion and Omnibus-Resistance Exercise Scale were taken following each trial. Reliability was quantified by coefficient of variation (CV), intra-class correlation coefficients (ICC), smallest worthwhile change (SWC), and standard error of the measurement. Results Metabolic and cardiovascular variables were highly reliable (≤ 5% CV; excellent-moderate ICC), while the respiratory variables demonstrated moderate reliability (< 8% CV; good-moderate ICC) across both conditions. Perceptual ratings had poorer reliability during the Control condition (12–45% CV; poor ICC) than the Patrol condition (7–16% CV; good ICC). Conclusions The test–retest reliability of metabolic and cardiovascular variables was high and relatively consistent during load carriage. Respiratory responses demonstrated moderate test–retest reliability; however, as the SWC differed with load carriage tasks, such data should be interpreted independently across loads. Perceptual measures demonstrated poor to moderate reliability during load carriage, and it is recommended that they only be employed as secondary measures. Graphical abstract

Managing offshore multi-use settings: Use of conceptual mapping to reduce uncertainty of co-locating seaweed aquaculture and wind farms - Ryan O'Shea; Elisa Capuzzo; Victoria Hemming; Gretchen Grebe; Rick Stafford; Sander W.K. van den Burg; Daniel Wood; Gordon Watson; Victoria Wells; Teresa Johnson; Stefan Erbs; Jaap W. van Hal; et al. (Journal of Environmental Management, 2024)

Differences in perceptions of COVID-19 risks in a fishing community in Alaska, 2020–2021 - M. Luke Smith; Guangqing Chi; Hannah Hennighausen; Davin Holen; E. Lance Howe (Marine Policy, 2024)

Sedimentary porewaters record regional tectonic and climate events that perturbed a deep-sea brine pool in the Gulf of Aqaba, Red Sea - Gaëlle Duchâtellier; Amanda M. Oehlert; Hannah Shernisky; Clément G.L. Pollier; Peter K. Swart; Bolton Howes; Sam J. Purkis (Science of The Total Environment, 2024)

Practice Is Evolving—a Briefing of the Revised 2024 Scopes and Standards of Practice - Susan Adams; Patricia Davidson; Erica Howes; Kimi McAdam; Christopher M. Messenger; Christopher Mills; Egondu M. Onuoha; Anna Marie Rodriguez; Christina Rollins; Dana Buelsing Sowards; Karen Hui; Carol J. Gilmore; et al. (Journal of the Academy of Nutrition and Dietetics, 2024)

Associations between area-level arsenic exposure and adverse birth outcomes: An Echo-wide cohort analysis - Jonathan V. Lewis; Emily A. Knapp; Shivani Bakre; Aisha S. Dickerson; Theresa M. Bastain; Casper Bendixsen; Deborah H. Bennett; Carlos A. Camargo; Andrea E. Cassidy-Bushrow; Elena Colicino; Viren D’Sa; Dana Dabelea; et al. (Environmental Research, 2023)

A review of new and existing non-extractive techniques for monitoring marine protected areas - Ryan McGeady; Robert M. Runya; James S. G. Dooley; John A. Howe; Clive J. Fox; Andrew J. Wheeler; Gerard Summers; Alexander Callaway; Suzanne Beck; Louise S. Brown; Gerard Dooly; Chris McGonigle (Frontiers in Marine Science, 2023)
Ocean biodiversity loss is being driven by several anthropogenic threats and significant efforts are required to halt losses and promote healthy marine ecosystems. The establishment of a network of Marine Protected Areas (MPAs) can help restrict damaging activities and have been recognised as a potential solution to aid marine conservation. When managed correctly they can deliver both ecological and socio-economic benefits. In recent times, MPA designations have increased rapidly while many countries have set future MPA targets for the decades ahead. An integral element of MPA management is adequate monitoring that collects data to assess if conservation objectives are being achieved. Data acquired by monitoring can vary widely as can the techniques employed to collect such data. Ideally, non-destructive and non-invasive methods are preferred to prevent damage to habitats and species, though this may rule out a number of traditional extractive sampling approaches such as dredges and trawls. Moreover, advances in ocean observation technologies enable the collection of large amounts of data at high resolutions, while automated data processing is beginning to make analyses more logistically feasible and less time-consuming. Therefore, developments to existing marine monitoring techniques and new emerging technologies have led to a diverse array of options when choosing to implement an MPA monitoring programme. Here, we present a review of new and existing non-extractive techniques which can be applied to MPA monitoring. We summarise their capabilities, applications, advantages, limitations and possible future developments. The review is intended to aid MPA managers and researchers in determining the suitability of available monitoring techniques based on data requirements and site conditions.

Editorial: The discovery of the unknown planet: the ocean - Paolo Favali; Juan José Dañobeitia; Bruce M. Howe; Henry A. Ruhl (Frontiers in Marine Science, 2023)

Metals and per- and polyfluoroalkyl substances mixtures and birth outcomes in the New Hampshire Birth Cohort Study: Beyond single-class mixture approaches - Gyeyoon Yim; Glen McGee; Lisa Gallagher; Emily Baker; Brian P. Jackson; Antonia M. Calafat; Julianne Cook Botelho; Diane Gilbert-Diamond; Margaret R. Karagas; Megan E. Romano; Caitlin G. Howe (Chemosphere, 2023)

Sex-specific effects of prenatal organophosphate ester (OPE) metabolite mixtures and adverse infant birth outcomes in the maternal and developmental risks from environmental and social stressors (MADRES) pregnancy cohort - Ixel Hernandez-Castro; Sandrah P. Eckel; Caitlin G. Howe; Zhongzheng Niu; Kurunthachalam Kannan; Morgan Robinson; Helen B. Foley; Brendan Grubbs; Laila Al-Marayati; Deborah Lerner; Nathana Lurvey; Max T. Aung; et al. (Environmental Research, 2023)

The benefits of regular aerobic exercise training on cerebrovascular function and cognition in older adults - Edward S. Bliss; Samia M. Biki; Rachel H. X. Wong; Peter R. C. Howe; Dean E. Mills (European Journal of Applied Physiology, 2023)
We compared the differences in cerebrovascular and cognitive function between 13 aerobic exercise trained, older adults and 13 age-, height- and sex-matched sedentary, untrained controls. We determined whether other measures accounted for differences in cerebrovascular and cognitive function between these groups and examined the associations between these functions. Participants undertook anthropometric, mood, cardiovascular, exercise performance, strength, cerebrovascular, and cognitive measurements, and a blood collection. Transcranial Doppler ultrasonography determined cerebrovascular responsiveness (CVR) to hypercapnia and cognitive stimuli. The trained group had a higher CVR to hypercapnia (80.3 ± 7.2 vs 35.1 ± 6.7%, P < 0.001), CVR to cognitive stimuli (30.1 ± 2.9 vs 17.8 ± 1.4%, P = 0.001) and total composite cognitive score (117 ± 2 vs 98 ± 4, P < 0.001) than the controls. These parameters no longer remained statistically different between the groups following adjustments for covariates. There were positive correlations between the total composite cognitive score and CVR to hypercapnia ( r = 0.474, P = 0.014) and CVR to cognitive stimuli ( r = 0.685, P < 0.001). We observed a relationship between cerebrovascular and cognitive function in older adults and an interaction between regular lifelong aerobic exercise training and cardiometabolic factors that may directly influence these functions.

Molecular characterisation and additional morphological descriptions of Eimeria spp. (Apicomplexa: Eimeriidae) from brown kiwi (Apteryx mantelli Bartlett) - Sarah M. Coker; Kate McInnes; Emilie Vallee; Patrick Biggs; William E. Pomroy; Laryssa Howe; Kerri J. Morgan (Systematic Parasitology, 2023)
Brown kiwi ( Apteryx mantelli Bartlett), a ratite endemic to New Zealand, is currently listed as “Vulnerable” under the IUCN classification system due to predation by introduced mammals. Operation Nest Egg (ONE) raises chicks and juveniles in predator-proof enclosures until they are large enough to defend themselves. These facilities experience an environmental accumulation of coccidial oocysts, which leads to severe morbidity and mortality of these kiwi. Four species of coccidia have been morphologically described from sporulated oocysts with additional opportunistic descriptions of endogenous stages. This research continues the morphological descriptions of these species of Eimeria with an additional novel morphotype also morphologically described. It also provides the first genetic characterisation targeting the mitochondrial cytochrome c oxidase I (COI) gene. Based on these findings, it was determined there are at least five morphotypes of Eimeria that infect brown kiwi and co-infections are common at the ONE facilities surveyed. The COI amplicon targeted for this study was sufficient to provide differentiation from other members of this genus. Sanger sequencing yielded ambiguous bases, indicating the need for more in-depth sequencing.

Prairie strips remove swine manure associated antimicrobial resistance genes and bacteria from runoff - Laura M. Alt; Jared S. Flater; Adina Howe; Thomas B. Moorman; Lisa A. Schulte; Michelle L. Soupir (Agriculture, Ecosystems & Environment, 2023)

A Numerical Study of SMART Cables Potential in Marine Hazard Early Warning for the Sumatra and Java Regions - Amir Salaree; Bruce M. Howe; Yihe Huang; Stuart A. Weinstein; Andi Eka Sakya (Pure and Applied Geophysics, 2023)

Consumer feces impact coral health in guild-specific ways - Carsten G. B. Grupstra; Lauren I. Howe-Kerr; Jesse A. van der Meulen; Alex J. Veglia; Samantha R. Coy; Adrienne M. S. Correa (Frontiers in Marine Science, 2023)
Animal waste products are an important component of nutrient cycles and result in the trophic transmission of diverse microorganisms. There is growing recognition that the feces of consumers, such as predators, may impact resource species, their prey, via physical effects and/or microbial activity. We tested the effect of feces from distinct fish trophic groups on coral health and used heat-killed fecal controls to tease apart physical versus microbial effects of contact with fecal material. Fresh grazer/detritivore fish feces caused lesions more frequently on corals, and lesions were 4.2-fold larger than those from sterilized grazer/detritivore feces; in contrast, fresh corallivore feces did not cause more frequent or larger lesions than sterilized corallivore feces. Thus, microbial activity in grazer/detritivore feces, but not corallivore feces, was harmful to corals. Characterization of bacterial diversity in feces of 10 reef fish species, ranging from obligate corallivores to grazer/detritivores, indicated that our experimental findings may be broadly generalizable to consumer guild, since feces of some obligate corallivores contained ~2-fold higher relative abundances of coral mutualist bacteria ( e.g., Endozoicomonadaceae), and lower abundances of the coral pathogen, Vibrio coralliilyticus , than feces of some grazer/detritivores. These findings recontextualize the ecological roles of consumers on coral reefs: although grazer/detritivores support coral reef health in various ways ( e.g. , promoting coral settlement and herbivory through the removal of detritus and sediments from the algal matrix), they also disperse coral pathogens. Corallivore predation can wound corals, yet their feces contain potentially beneficial coral-associated bacteria, supporting the hypothesized role of consumers, and corallivores in particular, in coral symbiont dispersal. Such consumer-mediated microbial dispersal as demonstrated here has broad implications for environmental management.

Investigating geological records of tsunamis in Western Thailand with environmental DNA - Wenshu Yap; Adam D. Switzer; Chris Gouramanis; Benjamin P. Horton; Ezequiel M. Marzinelli; Winona Wijaya; Yu Ting Yan; Dale Dominey-Howes; Maurizio Labbate; Kruawun Jankaew; Federico M. Lauro (Marine Geology, 2023)

How can diverse national food and land-use priorities be reconciled with global sustainability targets? Lessons from the FABLE initiative - Aline Mosnier; Guido Schmidt-Traub; Michael Obersteiner; Sarah Jones; Valeria Javalera-Rincon; Fabrice DeClerck; Marcus Thomson; Frank Sperling; Paula Harrison; Katya Pérez-Guzmán; Gordon Carlos McCord; Javier Navarro-Garcia; et al. (Sustainability Science, 2023)
There is an urgent need for countries to transition their national food and land-use systems toward food and nutritional security, climate stability, and environmental integrity. How can countries satisfy their demands while jointly delivering the required transformative change to achieve global sustainability targets? Here, we present a collaborative approach developed with the FABLE—Food, Agriculture, Biodiversity, Land, and Energy—Consortium to reconcile both global and national elements for developing national food and land-use system pathways. This approach includes three key features: (1) global targets, (2) country-driven multi-objective pathways, and (3) multiple iterations of pathway refinement informed by both national and international impacts. This approach strengthens policy coherence and highlights where greater national and international ambition is needed to achieve global goals (e.g., the SDGs). We discuss how this could be used to support future climate and biodiversity negotiations and what further developments would be needed.

Development of a High-Dose Infant Air-Jet Dry Powder Inhaler (DPI) with Passive Cyclic Loading of the Formulation - Connor Howe; Mohammad A. M. Momin; Ghali Aladwani; Michael Hindle; P. Worth Longest (Pharmaceutical Research, 2022)

Brain volume in chronic ketamine users — relationship to sub-threshold psychotic symptoms and relevance to schizophrenia - Robert A. Chesters; Fiona Pepper; Celia Morgan; Jonathan D. Cooper; Oliver D. Howes; Anthony C. Vernon; James M. Stone (Psychopharmacology, 2022)
Rationale Ketamine may model aspects of schizophrenia arising through NMDA receptor activity deficits. Although acute ketamine can induce effects resembling both positive and negative psychotic symptoms, chronic use may be a closer model of idiopathic psychosis. Objectives We tested the hypotheses that ketamine users had lower brain volumes, as measured using MRI, and greater sub-threshold psychotic symptoms relative to a poly-drug user control group. Methods Ketamine users (n = 17) and poly-drug using controls (n = 19) were included in the study. All underwent volumetric MRI imaging and measurement of sub-threshold psychotic symptoms using the Comprehensive Assessment of At-Risk Mental State (CAARMS). Freesurfer was used to analyse differences in regional brain volume, cortical surface area and thickness between ketamine users and controls. The relationship between CAARMS ratings and brain volume was also investigated in ketamine users. Results Ketamine users were found to have significantly lower grey matter volumes of the nucleus accumbens, caudate nucleus, cerebellum and total cortex (FDR p < 0.05; Cohen’s d = 0.36–0.75). Within the cortex, ketamine users had significantly lower grey matter volumes within the frontal, temporal and parietal cortices (Cohen’s d 0.7–1.31; FDR p < 0.05). They also had significantly higher sub-threshold psychotic symptoms (p < 0.05). Frequency of ketamine use showed an inverse correlation with cerebellar volume (p < 0.001), but there was no relationship between regional brain volumes and sub-threshold psychotic symptoms. Conclusions Chronic ketamine use may cause lower grey matter volumes as well as inducing sub-threshold psychotic symptoms, although these likely arise through distinct mechanisms.

The effects of AUT00206, a novel Kv3.1/3.2 potassium channel modulator, on task-based reward system activation: a test of mechanism in schizophrenia - Stephen J. Kaar; Ilinca Angelescu; Matthew M. Nour; Tiago Reis Marques; Alice Sharman; Anil Sajjala; John Hutchison; Philip McGuire; Charles Large; Oliver D. Howes (Psychopharmacology, 2022)
The pathophysiology of schizophrenia involves abnormal reward processing, thought to be due to disrupted striatal and dopaminergic function. Consistent with this hypothesis, functional magnetic resonance imaging (fMRI) studies using the monetary incentive delay (MID) task report hypoactivation in the striatum during reward anticipation in schizophrenia. Dopamine neuron activity is modulated by striatal GABAergic interneurons. GABAergic interneuron firing rates, in turn, are related to conductances in voltage-gated potassium 3.1 (Kv3.1) and 3.2 (Kv3.2) channels, suggesting that targeting Kv3.1/3.2 could augment striatal function during reward processing. Here, we studied the effect of a novel potassium Kv3.1/3.2 channel modulator, AUT00206, on striatal activation in patients with schizophrenia, using the MID task. Each participant completed the MID during fMRI scanning on two occasions: once at baseline, and again following either 4 weeks of AUT00206 or placebo treatment. We found a significant inverse relationship at baseline between symptom severity and reward anticipation-related neural activation in the right associative striatum ( r = -0.461, p = 0.035). Following treatment with AUT00206, there was a significant increase in reward anticipation-related activation in the left associative striatum (t (13) = 4.23, peak-level p (FWE) < 0.05)), but no significant effect in the ventral striatum. This provides preliminary evidence that the Kv3.1/3.2 potassium channel modulator, AUT00206, may address reward-related striatal abnormalities in schizophrenia.

Test–retest reliability of arterial spin labelling for cerebral blood flow in older adults with small vessel disease - Lauren R. Binnie; Mathilde M. H. Pauls; Philip Benjamin; Mohani-Preet K. Dhillon; Shai Betteridge; Brian Clarke; Rita Ghatala; Fearghal A. H. Hainsworth; Franklyn A. Howe; Usman Khan; Christina Kruuse; Jeremy B. Madigan; et al. (Translational Stroke Research, 2022)
Cerebral small vessel disease (SVD) is common in older people and is associated with lacunar stroke, white matter hyperintensities (WMH) and vascular cognitive impairment. Cerebral blood flow (CBF) is reduced in SVD, particularly within white matter. Here we quantified test–retest reliability in CBF measurements using pseudo-continuous arterial spin labelling (pCASL) in older adults with clinical and radiological evidence of SVD (N=54, mean (SD): 66.9 (8.7) years, 15 females/39 males). We generated whole-brain CBF maps on two visits at least 7 days apart (mean (SD): 20 (19), range 7-117 days). Test–retest reliability for CBF was high in all tissue types, with intra-class correlation coefficient [95%CI]: 0.758 [0.616, 0.852] for whole brain, 0.842 [0.743, 0.905] for total grey matter, 0.771 [0.636, 0.861] for deep grey matter (caudate-putamen and thalamus), 0.872 [0.790, 0.923] for normal-appearing white matter (NAWM) and 0.780 [0.650, 0.866] for WMH (all p<0.001). ANCOVA models indicated significant decline in CBF in total grey matter, deep grey matter and NAWM with increasing age and diastolic blood pressure (all p<0.001). CBF was lower in males relative to females (p=0.013 for total grey matter, p=0.004 for NAWM). We conclude that pCASL has high test–retest reliability as a quantitative measure of CBF in older adults with SVD. These findings support the use of pCASL in routine clinical imaging and as a clinical trial endpoint. All data come from the PASTIS trial, prospectively registered at: https://eudract.ema.europa.eu (2015-001235-20, registered 13/05/2015), http://www.clinicaltrials.gov (NCT02450253, registered 21/05/2015).

Striatal dopamine synthesis capacity and its association with negative symptoms upon resolution of positive symptoms in first-episode schizophrenia and delusional disorder - Stephanie M. Y. Wong; Y. N. Suen; Charlotte W. C. Wong; Sherry K. W. Chan; Christy L. M. Hui; W. C. Chang; Edwin H. M. Lee; Calvin P. W. Cheng; Garrett C. L. Ho; Gladys Goh Lo; Eric Y. L. Leung; Paul K. M. Au Yeung; et al. (Psychopharmacology, 2022)

Characterizing the Effects of Nasal Prong Interfaces on Aerosol Deposition in a Preterm Infant Nasal Model - Karl Bass; Mohammad A. M. Momin; Connor Howe; Ghali Aladwani; Sarah Strickler; Arun V. Kolanjiyil; Michael Hindle; Robert M. DiBlasi; Worth Longest (AAPS PharmSciTech, 2022)
The objective of this study was to characterize the effects of multiple nasal prong interface configurations on nasal depositional loss of pharmaceutical aerosols in a preterm infant nose-throat (NT) airway model. Benchmark in vitro experiments were performed in which a spray-dried powder formulation was delivered to a new preterm NT model with a positive-pressure infant air-jet dry powder inhaler using single- and dual-prong interfaces. These results were used to develop and validate a computational fluid dynamics (CFD) model of aerosol transport and deposition in the NT geometry. The validated CFD model was then used to explore the NT depositional characteristic of multiple prong types and configurations. The CFD model highlighted a turbulent jet effect emanating from the prong(s). Analysis of NT aerosol deposition efficiency curves for a characteristic particle size and delivery flowrate (3 µm and 1.4 L/min (LPM)) revealed little difference in NT aerosol deposition fraction (DF) across the prong insertion depths of 2–5 mm (DF = 16–24%) with the exception of a single prong with 5-mm insertion (DF = 36%). Dual prongs provided a modest reduction in deposition vs. a single aerosol delivery prong at the same flow for insertion depths Graphical Abstract

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The acute effects of cannabidiol on emotional processing and anxiety: a neurocognitive imaging study - Michael A. P. Bloomfield; Yumeya Yamamori; Chandni Hindocha; Augustus P. M. Jones; Jocelyn L. L. Yim; Hannah R. Walker; Ben Statton; Matthew B. Wall; Rachel H. Lees; Oliver D. Howes; Valerie H. Curran; Jonathan P. Roiser; et al. (Psychopharmacology, 2022)
Rationale There is growing interest in the therapeutic potential of cannabidiol (CBD) across a range of psychiatric disorders. CBD has been found to reduce anxiety during experimentally induced stress in anxious individuals and healthy controls. However, the mechanisms underlying the putative anxiolytic effects of CBD are unknown. Objectives We sought to investigate the behavioural and neural effects of a single dose of CBD vs. placebo on a range of emotion-related measures to test cognitive-mechanistic models of its effects on anxiety. Methods We conducted a randomised, double-blind, placebo-controlled, crossover, acute oral challenge of 600 mg of CBD in 24 healthy participants on emotional processing, with neuroimaging (viewing emotional faces during functional magnetic resonance imaging) and cognitive (emotional appraisal) measures as well as subjective response to experimentally induced anxiety. Results CBD did not produce effects on brain responses to emotional faces and cognitive measures of emotional processing, or modulate experimentally induced anxiety, relative to placebo. Conclusions Given the rising popularity of CBD for its putative medical benefits, these findings question whether further research is warranted to investigate the clinical potential of CBD for the treatment of anxiety disorders.

Nitrate enrichment has lineage specific effects on Pocillopora acuta adults, but no transgenerational effects in planulae - Marie E. Strader; Lauren I. Howe-Kerr; Jordan A. Sims; Kelly E. Speare; Amanda N. Shore; Deron E. Burkepile; Adrienne M. S. Correa (Coral Reefs, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Examining the impact of the Great Barrier Reef on tsunami propagation using numerical simulations - Mandi C. Thran; Sascha Brune; Jody M. Webster; Dale Dominey-Howes; Daniel Harris (Natural Hazards, 2021)

Queens of the inquiline social parasite Acromyrmex insinuator can join nest-founding queens of its host, the leaf-cutting ant Acromyrmex echinatior - J. Howe; M. Schiøtt; J. J. Boomsma (Insectes Sociaux, 2021)
Queens of the inquiline social parasite Acromyrmex insinuator are known to infiltrate mature colonies of Acromyrmex echinatior and to exploit the host’s perennial workforce by producing predominantly reproductive individuals while suppressing host reproduction. Here we report three cases of an A. insinuator queen having joined an incipient colony of A. echinatior that contained only the founding host-queen and her small symbiotic fungus garden. We conjectured that 1:1 host-inquiline co-founding—a phenomenon that has only rarely been reported in ants—may imply that the presence of an A. insinuator queen may incur benefits to the host by increasing survival of its incipient colonies. We observed that the parasite queens neither foraged nor defended the nest against intruders. However, the parasite queens interacted with the host and fungus in a way that could be consistent with grooming and/or with contributing eggs. These observations may help explain why A. insinuator queens have maintained metapleural glands, even though they are smaller than those of host queens, and why A. insinuator has lost the large foraging worker caste but not the small worker caste.

Corrigendum: On a Reef Far, Far Away: Anthropogenic Impacts Following Extreme Storms Affect Sponge Health and Bacterial Communities - Amanda Shore; Jordan A. Sims; Michael Grimes; Lauren I. Howe-Kerr; Carsten G. B. Grupstra; Shawn M. Doyle; Lauren Stadler; Jason B. Sylvan; Kathryn E. F. Shamberger; Sarah W. Davies; Lory Z. Santiago-Vázquez; Adrienne M. S. Correa (Frontiers in Marine Science, 2021)

Historic and Modern Approaches for the Discovery of Abandoned Wells for Methane Emissions Mitigation in Oil Creek State Park, Pennsylvania - Patricia M. B. Saint-Vincent; James I. Sams; Mumbi Mundia-Howe; Matthew D. Reeder; Garret A. Veloski; Natalie J. Pekney (Environmental Management, 2021)

On a Reef Far, Far Away: Anthropogenic Impacts Following Extreme Storms Affect Sponge Health and Bacterial Communities - Amanda Shore; Jordan A. Sims; Michael Grimes; Lauren I. Howe-Kerr; Carsten G. B. Grupstra; Shawn M. Doyle; Lauren Stadler; Jason B. Sylvan; Kathryn E. F. Shamberger; Sarah W. Davies; Lory Z. Santiago-Vázquez; Adrienne M. S. Correa (Frontiers in Marine Science, 2021)
Terrestrial runoff can negatively impact marine ecosystems through stressors including excess nutrients, freshwater, sediments, and contaminants. Severe storms, which are increasing with global climate change, generate massive inputs of runoff over short timescales (hours to days); such runoff impacted offshore reefs in the northwest Gulf of Mexico (NW GoM) following severe storms in 2016 and 2017. Several weeks after coastal flooding from these events, NW GoM reef corals, sponges, and other benthic invertebrates ∼185 km offshore experienced mortality (2016 only) and/or sub-lethal stress (both years). To assess the impact of storm-derived runoff on reef filter feeders, we characterized the bacterial communities of two sponges, Agelas clathrodes and Xestospongia muta , from offshore reefs during periods of sub-lethal stress and no stress over a three-year period (2016—2018). Sponge-associated and seawater-associated bacterial communities were altered during both flood years. Additionally, we found evidence of wastewater contamination (based on 16S rRNA gene libraries and quantitative PCR) in offshore sponge samples, but not in seawater samples, following these flood years. Signs of wastewater contamination were absent during the no-flood year. We show that flood events from severe storms have the capacity to reach offshore reef ecosystems and impact resident benthic organisms. Such impacts are most readily detected if baseline data on organismal physiology and associated microbiome composition are available. This highlights the need for molecular and microbial time series of benthic organisms in near- and offshore reef ecosystems, and the continued mitigation of stormwater runoff and climate change impacts.

Search for top‐down and bottom‐up drivers of latitudinal trends in insect herbivory in oak trees in Europe - Elena Valdés‐Correcher; Xoaquín Moreira; Laurent Augusto; Luc Barbaro; Christophe Bouget; Olivier Bouriaud; Manuela Branco; Giada Centenaro; György Csóka; Thomas Damestoy; Jovan Dobrosavljević; Mihai‐Leonard Duduman; et al. (Global Ecology and Biogeography, 2021)
Aim The strength of species interactions is traditionally expected to increase toward the Equator. However, recent studies have reported opposite or inconsistent latitudinal trends in the bottom‐up (plant quality) and top‐down (natural enemies) forces driving herbivory. In addition, these forces have rarely been studied together thus limiting previous attempts to understand the effect of large‐scale climatic gradients on herbivory. Location Europe. Time period 2018–2019. Major taxa studied Quercus robur . Methods We simultaneously tested for latitudinal variation in plant–herbivore–natural enemy interactions. We further investigated the underlying climatic factors associated with variation in herbivory, leaf chemistry and attack rates in Quercus robur across its complete latitudinal range in Europe. We quantified insect leaf damage and the incidence of specialist herbivores as well as leaf chemistry and bird attack rates on dummy caterpillars on 261 oak trees. Results Climatic factors rather than latitude per se were the best predictors of the large‐scale (geographical) variation in the incidence of gall‐inducers and leaf‐miners as well as in leaf nutritional content. However, leaf damage, plant chemical defences (leaf phenolics) and bird attack rates were not influenced by climatic factors or latitude. The incidence of leaf‐miners increased with increasing concentrations of hydrolysable tannins, whereas the incidence of gall‐inducers increased with increasing leaf soluble sugar concentration and decreased with increasing leaf C : N ratios and lignins. However, leaf traits and bird attack rates did not vary with leaf damage. Main conclusions These findings help to refine our understanding of the bottom‐up and top‐down mechanisms driving geographical variation in plant–herbivore interactions, and indicate the need for further examination of the drivers of herbivory on trees.

Publisher Correction to: Integrating adverse effect analysis into environmental risk assessment for exotic generalist arthropod biological control agents: a three-tiered framework - Débora P. Paula; David A. Andow; Barbara I. P. Barratt; Robert S. Pfannenstiel; Philippa J. Gerard; Jacqui H. Todd; Tania Zaviezo; Maria G. Luna; Claudia V. Cédola; Antoon J. M. Loomans; Andy G. Howe; Michael D. Day; et al. (BioControl, 2021)

Integrating adverse effect analysis into environmental risk assessment for exotic generalist arthropod biological control agents: a three-tiered framework - Débora P. Paula; David A. Andow; Barbara I. P. Barratt; Robert S. Pfannenstiel; Philippa J. Gerard; Jacqui H. Todd; Tania Zaviezo; Maria G. Luna; Claudia V. Cédola; Antoon J. M. Loomans; Andy G. Howe; Michael D. Day; et al. (BioControl, 2021)

Diet of the European bison (Bison bonasus) in a forest habitat estimated by DNA barcoding - Ida Hartvig; Andy G. Howe; Emilie N. B. Schmidt; Cino Pertoldi; Jeppe Lund Nielsen; Rita M. Buttenschøn (Mammal Research, 2021)

Symbiont community diversity is more variable in corals that respond poorly to stress - Lauren I. Howe‐Kerr; Benedicte Bachelot; Rachel M. Wright; Carly D. Kenkel; Line K. Bay; Adrienne M. S. Correa (Global Change Biology, 2020)
Coral reefs are declining globally as climate change and local water quality press environmental conditions beyond the physiological tolerances of holobionts—the collective of the host and its microbial symbionts. To assess the relationship between symbiont composition and holobiont stress tolerance, community diversity metrics were quantified for dinoflagellate endosymbionts (Family: Symbiodiniaceae) from eight Acropora millepora genets that thrived under or responded poorly to various stressors. These eight selected genets represent the upper and lower tails of the response distribution of 40 coral genets that were exposed to four stress treatments (and control conditions) in a 10‐day experiment. Specifically, four ‘best performer’ coral genets were analyzed at the end of the experiment because they survived high temperature, high p CO 2 , bacterial exposure, or combined stressors, whereas four ‘worst performer’ genets were characterized because they experienced substantial mortality under these stressors. At the end of the experiment, seven of eight coral genets mainly hosted Cladocopium symbionts, whereas the eighth genet was dominated by both Cladocopium and Durusdinium symbionts. Symbiodiniaceae alpha and beta diversity were higher in worst performing genets than in best performing genets. Symbiont communities in worst performers also differed more after stress exposure relative to their controls (based on normalized proportional differences in beta diversity), than did best performers. A generalized joint attribute model estimated the influence of host genet and treatment on Symbiodiniaceae community composition and identified strong associations among particular symbionts and host genet performance, as well as weaker associations with treatment. Although dominant symbiont physiology and function contribute to host performance, these findings emphasize the importance of symbiont community diversity and stochasticity as components of host performance. Our findings also suggest that symbiont community diversity metrics may function as indicators of resilience and have potential applications in diverse disciplines from climate change adaptation to agriculture and medicine.

Regional differences in aspen (Populus tremuloides Michx.) seedling response to an established nursery protocol - Alexander A. Howe; Simon M. Landhäusser; Owen T. Burney; James N. Long; Karen E. Mock (New Forests, 2020)

UBC-Nepal expedition: dynamic cerebral autoregulation is attenuated in lowlanders upon ascent to 5050 m - Michael M. Tymko; Alexander B. Hansen; Joshua C. Tremblay; Alexander Patrician; Ryan L. Hoiland; Connor A. Howe; Matthew G. Rieger; Philip N. Ainslie (European Journal of Applied Physiology, 2020)

Leveraging a Landscape-Level Monitoring and Assessment Program for Developing Resilient Shorelines throughout the Laurentian Great Lakes - Donald G. Uzarski; Douglas A. Wilcox; Valerie J. Brady; Matthew J. Cooper; Dennis A. Albert; Jan J. H. Ciborowski; Nicholas P. Danz; Anne Garwood; Joseph P. Gathman; Thomas M. Gehring; Greg P. Grabas; Robert W. Howe; et al. (Wetlands, 2019)

SMART Cables for Observing the Global Ocean: Science and Implementation - Bruce M. Howe; Brian K. Arbic; Jérome Aucan; Christopher R. Barnes; Nigel Bayliff; Nathan Becker; Rhett Butler; Laurie Doyle; Shane Elipot; Gregory C. Johnson; Felix Landerer; Stephen Lentz; et al. (Frontiers in Marine Science, 2019)

Observing the Oceans Acoustically - Bruce M. Howe; Jennifer Miksis-Olds; Eric Rehm; Hanne Sagen; Peter F. Worcester; Georgios Haralabus (Frontiers in Marine Science, 2019)

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

Dune soil communities primarily associated with climate factors, not exotic plant presence - Matthew L. Reid; Andrea S. Howes; Sarah M. Emery (Plant and Soil, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Meeting report: 31st International Mammalian Genome Conference, Mammalian Genetics and Genomics: From Molecular Mechanisms to Translational Applications - Gabriela Sánchez-Andrade; Jacob Moskowitz; Selene Howe; Teresa M. Gunn (Mammalian Genome, 2018)

The use of percentile-percentile plots to compare differences in seasonal dynamics, illustrated by the case of ground beetles (Coleoptera, Carabidae) reacting to urbanisation - G. L. Lövei; Z. Elek; A. Howe; M. Engaard (Community Ecology, 2018)

α5 nAChR modulation of the prefrontal cortex makes attention resilient - William M. Howe; Julie L. Brooks; Patrick L. Tierney; Jincheng Pang; Amie Rossi; Damon Young; Keith Dlugolenski; Ed Guillmette; Marc Roy; Katherine Hales; Rouba Kozak (Brain Structure and Function, 2018)

Scientific Considerations for the Assessment and Management of Mine Tailings Disposal in the Deep Sea - Lindsay L. Vare; Maria C. Baker; John A. Howe; Lisa A. Levin; Carlos Neira; Eva Z. Ramirez-Llodra; Amanda Reichelt-Brushett; Ashley A. Rowden; Tracy M. Shimmield; Stuart L. Simpson; Eulogio H. Soto (Frontiers in Marine Science, 2018)

Generation of transgenic goats by pronuclear microinjection: a retrospective analysis of a commercial operation (1995–2012) - W. Gavin; S. Blash; N. Buzzell; D. Pollock; L. Chen; N. Hawkins; J. Howe; K. Miner; J. Pollock; C. Porter; M. Schofield; Y. Echelard; et al. (Transgenic Research, 2018)

Multiple paternity in a Pacific marine turtle population: maternal attributes, offspring outcomes and demographic inferences - M. Howe; N. N. FitzSimmons; C. J. Limpus; S. M. Clegg (Marine Biology, 2018)

Influence of Local, Landscape, and Regional Variables on Sedge and Marsh Wren Occurrence in Great Lakes Coastal Wetlands - Hannah G. Panci; Gerald J. Niemi; Ronald R. Regal; Douglas C. Tozer; Thomas M. Gehring; Robert W. Howe; Christopher J. Norment (Wetlands, 2017)

Standardized Measures of Coastal Wetland Condition: Implementation at a Laurentian Great Lakes Basin-Wide Scale - Donald G. Uzarski; Valerie J. Brady; Matthew J. Cooper; Douglas A. Wilcox; Dennis A. Albert; Richard P. Axler; Peg Bostwick; Terry N. Brown; Jan J. H. Ciborowski; Nicholas P. Danz; Joseph P. Gathman; Thomas M. Gehring; et al. (Wetlands, 2017)

Summer temperature variability across four urban neighborhoods in Knoxville, Tennessee, USA - Kelsey N. Ellis; Jon M. Hathaway; Lisa Reyes Mason; David A. Howe; Thomas H. Epps; Vincent M. Brown (Theoretical and Applied Climatology, 2017)

Semiautomatic and Automatic Cooperative Inversion of Seismic and Magnetotelluric Data - Cuong V. A. Le; Brett D. Harris; Andrew M. Pethick; Eric M. Takam Takougang; Brendan Howe (Surveys in Geophysics, 2016)

A comparative approach to assess drivers of success in mammalian conservation recovery programs - Jennifer J. Crees; Amy C. Collins; P. J. Stephenson; Helen M. R. Meredith; Richard P. Young; Caroline Howe; Mark R. Stanley Price; Samuel T. Turvey (Conservation Biology, 2016)
The outcomes of species recovery programs have been mixed; high‐profile population recoveries contrast with species‐level extinctions. Each conservation intervention has its own challenges, but to inform more effective management it is imperative to assess whether correlates of wider recovery program success or failure can be identified. To contribute to evidence‐based improvement of future conservation strategies, we conducted a global quantitative analysis of 48 mammalian recovery programs. We reviewed available scientific literature and conducted semistructured interviews with conservation professionals involved in different recovery programs to investigate ecological, management, and political factors associated with population recoveries or declines. Identifying and removing threats was significantly associated with increasing population trend and decreasing conservation dependence, emphasizing that populations are likely to continue to be compromised in the absence of effective threat mitigation and supporting the need for threat monitoring and adaptive management in response to new and potential threats. Lack of habitat and small population size were cited as limiting factors in 56% and 42% of recovery programs, respectively, and both were statistically associated with increased longer term dependence on conservation intervention, demonstrating the importance of increasing population numbers quickly and restoring and protecting habitat. Poor stakeholder coordination and management were also regularly cited by respondents as key weaknesses in recovery programs, indicating the importance of effective leadership and shared goals and management plans. Project outcomes were not influenced by biological or ecological variables such as body mass or habitat, which suggests that these insights into correlates of conservation success and failure are likely to be generalizable across mammals.

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Coastal soft cliff invertebrates are reliant upon dynamic coastal processes - M. A. Howe (Journal of Coastal Conservation, 2015)

MAM (E17) rodent developmental model of neuropsychiatric disease: disruptions in learning and dysregulation of nucleus accumbens dopamine release, but spared executive function - William M. Howe; Patrick L. Tierney; Damon A. Young; Charlotte Oomen; Rouba Kozak (Psychopharmacology, 2015)

Analytic laboratory performance of a point of care urine culture kit for diagnosis and antibiotic susceptibility testing - E. Bongard; N. Frimodt-Møller; M. Gal; M. Wootton; R. Howe; N. Francis; H. Goossens; C. C. Butler (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Further human evidence for striatal dopamine release induced by administration of ∆9-tetrahydrocannabinol (THC): selectivity to limbic striatum - Matthijs G. Bossong; Mitul A. Mehta; Bart N. M. van Berckel; Oliver D. Howes; René S. Kahn; Paul R. A. Stokes (Psychopharmacology, 2015)

How functional traits, herbivory, and genetic diversity interact in Echinacea : implications for fragmented populations - Pamela M. Kittelson; Stuart Wagenius; Reina Nielsen; Sanjive Qazi; Michael Howe; Gretel Kiefer; Ruth G. Shaw (Ecology, 2015)
Habitat fragmentation produces small, spatially isolated populations that promote inbreeding. Remnant populations often contain inbred and outbred individuals, but it is unclear how inbreeding relative to outbreeding affects the expression of functional traits and biotic interactions such as herbivory. We measured a suite of 12 functional traits and herbivore damage on three genotypic cross types in the prairie forb, Echinacea angustifolia : inbred, and outbred crosses resulting from matings within and between remnant populations. Inbreeding significantly affected the expression of all 12 functional traits that influence resource capture. Inbred individuals had consistently lower photosynthetic rates, water use efficiencies, specific leaf areas, and had higher trichome numbers, percent C, and percent N than outbred individuals. However, herbivore damage did not differ significantly among the cross types and was not correlated with other leaf functional traits. Leaf architecture and low physiological rates of the inbred compared to outbred individuals imply poorer capture or use of resources. Inbred plants also had lower survival and fitness relative to outbred plants. Our results show that inbreeding, a phenomenon predicted and observed to occur in fragmented populations, influences key functional traits such as plant structure, physiology and elemental composition. Because of their likely role in fitness of individuals and ecological dynamics plant functional traits can serve as a bridge between evolution and community or ecosystem ecology.

Regional Forcing by Light on Dissolved Oxygen Levels in Shallow Temperate Estuaries - Anna M. Sawabini; David R. Schlezinger; Miles A. Sundermeyer; Brian L. Howes (Estuaries and Coasts, 2015)

Development of an Integrated Surface Stimulation Device for Systematic Evaluation of Wound Electrotherapy - D. S. Howe; J. Dunning; C. Zorman; S. L. Garverick; K. M. Bogie (Annals of Biomedical Engineering, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Gene expression accurately distinguishes liver metastases of small bowel and pancreas neuroendocrine tumors - Scott K. Sherman; Jessica E. Maxwell; Jennifer C. Carr; Donghong Wang; Andrew M. Bellizzi; M. Sue O’Dorisio; Thomas M. O’Dorisio; James R. Howe (Clinical & Experimental Metastasis, 2014)

Growth performance and chestnut blight incidence (Cryphonectria parasitica) of backcrossed chestnut seedlings in surface mine restoration - Jenise M. Bauman; Carolyn Howes Keiffer; Brian C. McCarthy (New Forests, 2014)

Re‐evaluation of the Roseau Tuff eruptive sequence and other ignimbrites in Dominica, Lesser Antilles - TRACY M. HOWE; JAN M. LINDSAY; PHIL SHANE; AXEL K. SCHMITT; DANIEL F. STOCKLI (Journal of Quaternary Science, 2014)
The island of Dominica hosts several ignimbrites, including the Roseau Tuff, thought to represent the largest eruption in the Caribbean in the past 200 000 years. The volcanic stratigraphy of the island is poorly understood due to limited outcrops and a paucity of geochemical and geochronological data. The discovery of a new fully accessible exposure of three ignimbrites intercalated with paleosols provides an opportunity to re‐evaluate the current stratigraphic framework of ignimbrite‐forming eruptions on the island. Whole‐rock analyses of pumice clasts from Dominica ignimbrites are andesitic (61–66% SiO 2 ) and in most cases are geochemically indistinguishable. Ignimbrites in the north of the island have less evolved glass compositions (73–75% SiO 2 ) and more mafic orthopyroxene compositions (En > 56) than their southern counterparts (75–78% SiO 2 ; En

Cycloserine as an alternative urinary tract infection therapy: susceptibilities of 500 urinary pathogens to standard and alternative therapy antimicrobials - R. Kugathasan; M. Wootton; R. Howe (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Erratum to: Glutamate, N-acetyl aspartate and psychotic symptoms in chronic ketamine users - James M. Stone; Fiona Pepper; Johnson Fam; Hannah Furby; Emer Hughes; Celia Morgan; Oliver D. Howes (Psychopharmacology, 2014)

Glutamate, N-acetyl aspartate and psychotic symptoms in chronic ketamine users - James M. Stone; Fiona Pepper; Johnson Fam; Hannah Furby; Emer Hughes; Celia Morgan; Oliver D. Howes (Psychopharmacology, 2014)

Coastal dune stabilization in Wales and requirements for rejuvenation - K. Pye; S. J. Blott; M. A. Howe (Journal of Coastal Conservation, 2014)

The native–invasive balance: implications for nutrient cycling in ecosystems - Jonathan E. Hickman; Isabel W. Ashton; Katherine M. Howe; Manuel T. Lerdau (Oecologia, 2013)

Knee extensor strength differences in obese and healthy-weight 10-to 13-year-olds - Margarita D. Tsiros; Alison M. Coates; Peter R. C. Howe; Paul N. Grimshaw; Jeff Walkley; Anthony Shield; Richard Mallows; Andrew P. Hills; Masaharu Kagawa; Sarah Shultz; Jonathan D. Buckley (European Journal of Applied Physiology, 2013)

Associative blocking to reward-predicting cues is attenuated in ketamine users but can be modulated by images associated with drug use - Tom P. Freeman; Celia J. A. Morgan; Fiona Pepper; Oliver D. Howes; James M. Stone; H. Valerie Curran (Psychopharmacology, 2013)

Conifer DBMagic: a database housing multiple de novo transcriptome assemblies for 12 diverse conifer species - W. Walter Lorenz; Savavanaraj Ayyampalayam; John M. Bordeaux; Glenn T. Howe; Kathleen D. Jermstad; David B. Neale; Deborah L. Rogers; Jeffrey F. D. Dean (Tree Genetics & Genomes, 2012)

Detecting arthropod intraguild predation in the field - Alexandre Aebi; Peter M. J. Brown; Patrick De Clercq; Louis Hautier; Andy Howe; Brecht Ingels; Hans-Peter Ravn; John J. Sloggett; Renate Zindel; Alison Thomas (BioControl, 2011)

The importance of coastal sand dunes for terrestrial invertebrates in Wales and the UK, with particular reference to aculeate Hymenoptera (bees, wasps & ants) - M. A. Howe; G. T. Knight; C. Clee (Journal of Coastal Conservation, 2010)

Tissue stretch induces nuclear remodeling in connective tissue fibroblasts - Helene M. Langevin; Kirsten N. Storch; Robert R. Snapp; Nicole A. Bouffard; Gary J. Badger; Alan K. Howe; Douglas J. Taatjes (Histochemistry and Cell Biology, 2010)

Do estuaries pose a toxic contamination risk for wading birds? - J. T. Smith; L. A. Walker; R. F. Shore; S. E. A. le V. dit Durell; P. D. Howe; M. Taylor (Ecotoxicology, 2009)

Salt marshes and eutrophication: An unsustainable outcome - R. Eugene Turner; Brian L. Howes; John M. Teal; Charles S. Milan; Erick M. Swenson; Dale D. Goehringer‐ Tonerb (Limnology and Oceanography, 2009)
Most plant production by emergent coastal marshes occurs belowground. This belowground production adds to the accumulation of organic matter sustaining salt marshes as sea level rises, thus preventing excessive flooding, eventual plant death, and habitat loss. The ubiquitous nutrient enrichment of coastal salt marshes stimulating aboveground plant growth may result in higher rates of inorganic matter accumulation that compensates for marsh flooding caused by sea level rise. Results from several short‐term experiments, however, demonstrate that root and rhizome biomass and carbon accumulation is reduced with nutrient enrichment, suggesting that eutrophication of coastal waters may not be a compensatory counterbalance to the effects of global sea level rise on salt marshes. We show that the net effects of 36 yr of nutrient enrichment in replicated field experiments do not lead to higher organic or inorganic accumulation. Enrichment reduces organic matter belowground and may result in a significant loss in marsh elevation equivalent to about half the average global sea level rise rates. Sustaining and restoring coastal emergent marshes is more likely if they receive less, not more, nutrient loading.

Dynamics of Campylobacter colonization of a natural host, Sturnus vulgaris (European Starling) - F. M. Colles; N. D. McCarthy; J. C. Howe; C. L. Devereux; A. G. Gosler; M. C. J. Maiden (Environmental Microbiology, 2009)
Summary Wild European Starlings ( Sturnus vulgaris ) shed Campylobacter at high rates, suggesting that they may be a source of human and farm animal infection. A survey of Campylobacter shedding of 957 wild starlings was undertaken by culture of faecal specimens and genetic analysis of the campylobacters isolated: shedding rates were 30.6% for Campylobacter jejuni , 0.6% for C. coli and 6.3% for C. lari. Genotyping by multilocus sequence typing (MLST) and antigen sequence typing established that these bacteria were distinct from poultry or human disease isolates with the ST‐177 and ST‐682 clonal complexes possibly representing starling‐adapted genotypes. There was seasonal variation in both shedding rate and genotypic diversity, both exhibiting a maximum during the late spring/early summer. Host age also affected Campylobacter shedding, which was higher in younger birds, and turnover was rapid with no evidence of cross‐immunity among Campylobacter species or genotypes. In nestlings, C. jejuni shedding was evident from 9 days of age but siblings were not readily co‐infected. The dynamics of Campylobacter infection of starlings differed from that observed in commercial poultry and consequently there was no evidence that wild starlings represent a major source of Campylobacter infections of food animals or humans.

Effects of experimental manipulation of light and nutrients on establishment of seedlings of native and invasive woody species in Long Island, NY forests - Jessica Gurevitch; Timothy G. Howard; Isabel W. Ashton; Elizabeth A. Leger; Katherine M. Howe; Eliza Woo; Manuel Lerdau (Biological Invasions, 2008)

The Interaction between Soil Nutrients and Leaf Loss during Early Establishment in Plant Invasion - Elizabeth A. Leger; Katherine M. Howe; Jessica Gurevitch; Eliza Woo; Jonathan Hickman; Isabel W. Ashton; Manuel Lerdau (Forest Science, 2007)
Nitrogen availability affects both plant growth and the preferences of herbivores. We hypothesized that an interaction between these two factors could affect the early establishment of native and exotic species differently, promoting invasion in natural systems. Taxonomically paired native and invasive species (Acer platanoides, Acer rubrum, Lonicera maackii, Diervilla lonicera, Celastrus orbiculata, Celastrus scandens, Elaeagnus umbellata, Ceanothus americanus, Ampelopsis brevipedunculata, and Vitis riparia) were grown in relatively high-resource (hardwood forests) and low-resource (pine barrens) communities on Long Island, New York, for a period of 3 months. Plants were grown in ambient and nitrogen-enhanced conditions in both communities. Nitrogen additions produced an average 12% initial increase in leaf number of all plants. By the end of the experiment, invasive species outperformed native species in nitrogen-enhanced plots in hardwood forests, where all plants experienced increased damage relative to control plots. Native species experienced higher overall amounts of damage in hardwood forests, losing, on average, 45% more leaves than exotic species, and only native species experienced a decline in growth rates (32% compared with controls). In contrast, in pine barrens, there were no differences in damage and no differences in performance between native and invasive plants. Our results suggest that unequal damage by natural enemies may play a role in determining community composition by shifting the competitive advantage to exotic species in nitrogen-enhanced environments.

Integrated Measures of Anthropogenic Stress in the U.S. Great Lakes Basin - Nicholas P. Danz; Gerald J. Niemi; Ronald R. Regal; Tom Hollenhorst; Lucinda B. Johnson; JoAnn M. Hanowski; Richard P. Axler; Jan J. H. Ciborowski; Thomas Hrabik; Valerie J. Brady; John R. Kelly; John A. Morrice; et al. (Environmental Management, 2007)

Litter hovels as havens for riparian spiders in an unregulated river - Matthew R. Loeser; Bradner H. McRae; Marisa M. Howe; Thomas G. Whitham (Wetlands, 2006)

Insights into the role of the histidines in the structure and stability of cytochrome c - Federica Sinibaldi; Barry D. Howes; M Cristina Piro; Paola Caroppi; Giampiero Mei; Franca Ascoli; Giulietta Smulevich; Roberto Santucci (JBIC Journal of Biological Inorganic Chemistry, 2006)

The use of cover crops in cereal-based cropping systems to control nitrate leaching in SE England - A. J. Macdonald; P. R. Poulton; M. T. Howe; K. W. T. Goulding; D. S. Powlson (Plant and Soil, 2005)

Cutaneous metabolism of glycol ethers - David J. Lockley; Douglas Howes; Faith M. Williams (Archives of Toxicology, 2005)

Percutaneous penetration and metabolism of 2-butoxyethanol - David J. Lockley; Douglas Howes; Faith M. Williams (Archives of Toxicology, 2004)

Characterization of P lys -proximal morphogenetic genes of transposable bacteriophage Mu - F. Sieder; K. Kumar; M. M. Howe; M. S. DuBow; I. R. Siboo (Archives of Virology, 2004)

Experimental investigation of taxon‐specific response of alkaline phosphatase activity in natural freshwater phytoplankton - K. Rengefors; K. C. Ruttenberg; C. L. Haupert; C. Taylor; B. L. Howes; D. M. Anderson (Limnology and Oceanography, 2003)
It is widely accepted that alkaline phosphatase activity (APA) is an efficient indicator of phosphate limitation in freshwater phytoplankton communities. In this study, we investigated whether the response in APA to phosphate limitation differs among the taxa in a mixed phytoplankton assemblage. We used the new enzyme‐labeled fluorescence (ELF) technique, which allows microscopic detection of phosphate limitation in individual cells of multiple species. The most prominent findings of this study were that alkaline phosphatase (AP) was induced in many, but not all taxa and that different taxa, as well as different cells within a single taxon, experienced different degrees of phosphate stress under the same environmental conditions. Our approach was to manipulate the limiting nutrient in a natural freshwater phytoplankton community by incubating lake water in the laboratory. We induced nitrogen (N) or phosphate limitation through additions of inorganic nutrients. Both the ELF assay and bulk APA indicated that the lake phytoplankton were not phosphate limited at the start of the experiment. During the experiment, several chlorophyte taxa (e.g., Eudorina and an unidentified solitary spiny coccoid) were driven to phosphate limitation when inorganic N was added, as evidenced by a higher percentage of ELF‐labeled cells relative to controls, whereas other chlorophyte taxa such as Actinastrum and Dictyosphaerium were not phosphate stressed under these conditions. In the phosphate‐limited treatments, little or no ELF labeling was observed in any cyanobacterial taxa. Furthermore, all taxa observed after the ELF labeling procedure (

The research potential of tissue from a cadaveric donor - Christopher Womack; Neil M. Gray; Lesley J. Howes; Michael D. Harris (Cell and Tissue Banking, 2002)

Formation of two types of low-spin heme in horseradish peroxidase isoenzyme A2 at low temperature - B. D. Howes; A. Feis; C. Indiani; M. P. Marzocchi; G. Smulevich (JBIC Journal of Biological Inorganic Chemistry, 2000)

Geological and Historical Investigation of the 1650 Mt. Columbo (Thera Island) Eruption and Tsunami, Aegean Sea, Greece - D. T. M. Dominey-Howes; G. A. Papadopoulos; A. G. Dawson (Natural Hazards, 2000)

Variation in quality and decomposability of red oak leaf litter along an urban-rural gradient - M. M. Carreiro; K. Howe; D. F. Parkhurst; R. V. Pouyat (Biology and Fertility of Soils, 1999)

O2 uptake during solid-state fermentation in a rotating drum bioreactor - Anna J. Marsh; David A. Mitchell; Deidre M. Stuart; Tony Howes (Biotechnology Letters, 1998)

Annual cycles of phytoplankton community-structure and bloom dynamics in the Neuse River Estuary, North Carolina - J. L. Pinckney; H. W. Paerl; M. B. Harrington; K. E. Howe (Marine Biology, 1998)

Dissolved gas dynamics in perennially ice‐covered Lake Fryxell, Antarctica - E. M. Hood; B. L. Howes; W. J. Jenkins (Limnology and Oceanography, 1998)
We use the concentrations of noble gases (He, Ne, and Ar), helium isotopes, and tritium to characterize the mechanisms and rates of ventilation for Lake Fryxell, Antarctica, as well as the physical processes controlling dissolved gases. The upper oxic zone is ventilated on timescales of several decades. The anoxic bottom waters are weakly ventilated, with a turnover time of ∼3,800 years. In the upper euphotic zone, helium and neon are greatly undersaturated with respect to solubility equilibrium with the atmosphere, whereas argon is greatly supersaturated owing to equilibrium partitioning of the gases between ice, water, and air inclusions in the ice. In the bottom waters, the inert dissolved gas concentrations may be remnants of a near‐desiccation event that occurred ∼2,000 years B.P., consistent with current paleoclimatic theories.

Design of a summary screen for an ICU patient data management system - R. H. Ireland; H. V. James; M. Howes; A. J. Wilson (Medical & Biological Engineering & Computing, 1997)

The relationship between dietary fat intake and risk of colorectal cancer: evidence from the combined analysis of 13 case-control studies - Geoffrey R. Howe; Kristan J. Aronson; Enrique Benito; Roberto Castelleto; Jacqueline Cornée; Stephen Duffy; Richard P. Gallagher; José M. Iscovich; Jiao Deng-ao; Rudolf Kaaks; Gabriel A. Kune; Susan Kune; et al. (Cancer Causes & Control, 1997)

Prediction of the percutaneous penetration and metabolism of dodecyl decaethoxylate in rats using in vitro models - Clive S. Roper; Doug Howes; Peter G. Blain; Faith M. Williams (Archives of Toxicology, 1995)

Flavivirus West Nile (Sarafend) egress at the plasma membrane - M. L. Ng; J. Howe; V. Sreenivasan; J. J. L. Mulders (Archives of Virology, 1994)

A recombinant fowlpox virus that expresses the VP2 antigen of infectious bursal disease virus induces protection against mortality caused by the virus - C. D. Bayliss; R. W. Peters; Jane K. A. Cook; R. L. Reece; K. Howes; M. M. Binns; M. E. G. Boursnell (Archives of Virology, 1991)

Effect of carbon source on enzymes involved in glycerol metabolism inNeurospora crassa - Gary D. Tom; M. Viswanath-Reddy; H. Branch Howe (Archives of Microbiology, 1978)